Glutamate potentiates susceptibility of P. aeruginosa clinical isolates to gentamycin: a new adjuvant hope for an old antibiotic - Nageeb, Wedad M.; Hetta, Helal F.; Frampton, Dan; Saunders, Nigel J. (Frontiers in Microbiology, 2026)
Aminoglycosides have long been considered essential agents in P. aeruginosa chemotherapy; however, resistance is on the rise. Glutamate is a crucial molecule for all living organisms, serving a fundamental function in various metabolic activities. A deeper comprehension of metabolic flux may facilitate effective therapeutic strategies for the eradication of antibiotic-resistant microorganisms. In this work, we aim to investigate a novel approach of amino acid-antibiotic adjuvant to potentiate activity of existing therapeutics through a low-toxicity adjuvant strategy offering lower risk of unwanted effects. We used 25 P. aeruginosa whole-genome sequenced clinical isolates selected from a genomically diverse set of isolates. The effect of glutamate-gentamycin combination on bacterial growth was tested. The effect of gentamycin-glutamate combination on outer membrane permeability was also studied using NPN. GWAS analysis was implemented using Pyseer to investigate genes underlying the observed enhanced effect of glutamate/gentamycin combination on bacterial killing. Among the tested 25 P. aeruginosa isolates, fifteen isolates demonstrated enhanced combinatorial effect of the gentamycin-glutamate combination resulting in enhanced bacterial killing effect. Interestingly observed, a set of genes involved in glycerophospholipid metabolism, purine metabolism, and glutamate metabolic pathways were interconnected showing significant differences among the two phenotypic groups using Pyseer. The uptake of fluorophore NPN in the presence of glutamate and two sub-inhibitory concentrations of gentamycin was increased indicating increased membrane permeabilization. This study reports the enhanced antibacterial effect of gentamycin-glutamate combination against P. aeruginosa opening doors for novel alternative treatment approaches against drug-resistant bacteria. Metabolic reprogramming offers a promising potential to enhance antibiotic mediated bacterial killing.